Dual functions of Lactobacillus acidophilus NCFM(™) at the intermediate dose in protection against rotavirus diarrhea in gnotobiotic pigs vaccinated with a human rotavirus vaccine - Liu, Fangning (2014)
OBJECTIVES: To examine dose effects of Lactobacillus acidophilus NCFM (LA) (™) strain on rotavirus-specific antibody and B cell responses in gnotobiotic pigs vaccinated with an oral attenuated human rotavirus (AttHRV). METHODS: Pigs were inoculated with AttHRV vaccine in conjunction with high dose LA (14 doses, total 2.2×10(9) colony forming units [CFU]), intermediate dose LA (9 doses, total 3.2×10(6) CFU), low dose LA (5 doses, total 2.1×10(6) CFU) or without LA feeding. Protection against rotavirus shedding and diarrhea was assessed upon challenge with a virulent HRV. Rotavirus-specific IgA and IgG antibodies in serum and rotavirus-specific IgA and IgG antibody-secreting cells (ASC) and memory B cells in ileum, spleen and blood of the pigs were measured and compared among treatment groups. RESULTS: The intermediate dose LA (MidLA), but not high or low dose LA, significantly reduced rotavirus diarrhea (MidLA only group) and significantly improved the protection conferred by AttHRV vaccine (MidLA+AttHRV group). Associated with the increased protection, MidLA significantly enhanced rotavirus-specific antibody, ASC and memory B cell responses to AttHRV vaccine. High or low dose LA did not enhance virus-specific antibody and ASC responses, hence did not improve the vaccine efficacy. CONCLUSIONS: These findings highlight the importance of dose selection and indicate that certain specific lactobacilli strains at the appropriate dose have the dual function of reducing rotavirus diarrhea and enhancing the immunogenicity and protective efficacy of rotavirus vaccines.